2017
DOI: 10.15171/bi.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular machineries of pH dysregulation in tumor microenvironment: potential targets for cancer therapy

Abstract: Introduction: Cancer is an intricate disorder/dysfunction of cells that can be defined as a genetic heterogeneity in human disease. Therefore, it is characterized by several adaptive complex hallmarks. Among them, the pH dysregulation appears as a symbol of aberrant functions within the tumor microenvironment (TME). In comparison with normal tissues, in the solid tumors, we face with an irregular acidification and alkalinization of the extracellular and intracellular fluids. Methods: In this study, we compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 178 publications
(155 reference statements)
0
82
0
Order By: Relevance
“…Such acidic steady-state pH i value is not only significantly lower than that of highly proliferated cells, i.e. embryonic stem cells and cancer cells (~7.4) [43,46,47], but also lower than that of normal animal and human mature cells (~7.2) [23-25, 28, 48]. As steady-state pH i is a balance through the combined operation of passive intracellular buffering power and active transmembrane pH i transporters [24][25][26], therefore, the shift of ~0.4 pH i units from alkaline to acidic means a dramatic kinetic change in the pH i regulating mechanism.…”
Section: The Resting Ph I and New Steady-state Ph I In Oec-m1 Cellsmentioning
confidence: 93%
“…Such acidic steady-state pH i value is not only significantly lower than that of highly proliferated cells, i.e. embryonic stem cells and cancer cells (~7.4) [43,46,47], but also lower than that of normal animal and human mature cells (~7.2) [23-25, 28, 48]. As steady-state pH i is a balance through the combined operation of passive intracellular buffering power and active transmembrane pH i transporters [24][25][26], therefore, the shift of ~0.4 pH i units from alkaline to acidic means a dramatic kinetic change in the pH i regulating mechanism.…”
Section: The Resting Ph I and New Steady-state Ph I In Oec-m1 Cellsmentioning
confidence: 93%
“…However, the chemical cleavage of a pH-responsive substructure is not fast enough, resulting in slow response speed [ 62 ]. Recent studies have reported that tumor cells not only acidify but also alkalize, in which situation pH-responsive drug delivery systems do not apply [ 65 , 66 ]. Enzyme-responsive drug delivery systems have been recognized as a valuable strategy to achieve efficient intracellular drug delivery [ 67 , 68 ], as there are abundant enzymes including proteases, matrix metalloproteinases and hyaluronidases in the lysosomes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pH plays an important role in physiological environments, regulating cellular functions and physiological activities. The pH dysregulation in intracellular fluids is related to tumorigenesis and drug‐resistance . Real‐time sensing and monitoring of pH changes inside live cells are therefore important for probing disease mechanisms and designing pH‐responsive intracellular drug delivery systems.…”
Section: Nmofs For Imaging and Biosensingmentioning
confidence: 99%